Improvement Of Material Quality In The Warehouse Using The Failure Mode And Effect Analysis (FMEA) And 5W+1H Methods At PT XYZ - Mukti Hidayat; Rudy Effendi Listyanto; Purnama Sakhrial Pradini (CV. AFDIFAL MAJU BERKAH, 2026)
PT. XYZ is a manufacturing company specializing in the production of disc brakes and mufflers. This study identifies issues within the management of the M2FW Raw Material warehouse at PT. XYZ, stemming from the suboptimal implementation of the First-In, First-Out (FIFO) system. The failure to maintain an effective FIFO system has led to several serious problems, including material damage due to corrosion, discrepancies between recorded data and actual physical stock, and poor warehouse maintenance regarding cleanliness and organization. These findings underscore the urgent need for systemic and procedural improvements to ensure operational efficiency and prevent further losses.This research utilizes a quantitative descriptive approach using the Failure Mode and Effect Analysis (FMEA) method to evaluate failure risks, alongside a 5W+1H analysis to identify root causes. Data collection results during the research indicate the presence of 465 pieces of Not Good (NG) products (0.17% of total stock) with total losses reaching IDR 8,688,270.97, as well as a physical stock discrepancy of 302 pieces. Based on the FMEA analysis, work methods that deviate from standard operating procedures were identified as the most critical failure factor, yielding the highest Risk Priority Number (RPN) of 270. Applying a Kaizen approach, the proposed improvements include: standardizing methods through daily checksheets for 5S and FIFO control; implementing a structured warehouse area monitoring schedule; and categorizing supplier delivery schedules based on part size (small, medium, large) to streamline the storage process. The implementation of these steps is expected to minimize financial losses, improve stock data accuracy, and ensure operational fluidity in accordance with Standard Operating Procedures (SOP).